Association between insulin receptor substrate-1 polymorphisms and high platelet reactivity with clopidogrel therapy in coronary artery disease patients with type 2 diabetes mellitus. Issue 1 (December 2016) - Zhang, Dingyu; Zhang, Xiaolin; Liu, Dan; Liu, Tengfei; Cai, Wenzhi; Yan, Chenghui; Han, Yaling
Abstract Background The mechanisms leading to the high on-treatment platelet reactivity in diabetes patients are not fully elucidated. The genetic factors may be associated with the diminished antiplatelet efficacy of dual antiplatelet therapy. We investigated the possible association between insulin receptor substrate-1 (IRS-1) polymorphisms and high platelet reactivity in coronary artery disease (CAD) patients with type 2 diabetes mellitus (T2DM). Methods A total of 674 CAD patients with T2DM were enrolled in this study. Platelet aggregation and platelet activation were assessed with light transmission aggregometry and flow cytometry analysis, respectively. Participants were divided into high platelet reactivity (HPR) group and non-HPR group according to their maximal platelet aggregation. Genotypes were identified by polymerase chain reaction and direct sequencing of genomic DNA. The association between IRS-1 genetic variants and platelet function was assessed. Results There were 233 participants in the HPR group and 441 participants in the non-HPR group. G allele frequencies of rs13431554 were 27.7 % for the HPR group and 18.6 % for the non-HPR group (p < 0.001). Adenosine diphosphate and arachidonic acid induced platelet aggregation were significantly higher in G allele carriers compared with non-carriers (56.8 ± 16.2 vs 52.0 ± 17.9 %, p < 0.01, 28.9 ± 18.6 vs 25.2 ± 17.8 %, p < 0.01, respectively). We observed that P-selectin expression and PAC-1 binding were higher in G allele carriers compared with non-carriers (40.8 ± 12.4 vs 36.2 ± 13.8, p = 0.01; 43.7 ± 15.9 vs 38.7 ± 19.9, p = 0.03, respectively). Conclusion The G allele of rs13431554 in the IRS-1 gene was associated with a hyperreactive platelet phenotype in the CAD patients with T2DM.